2017
DOI: 10.1108/tqm-03-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory analysis of quality costing in Greek F&B enterprises

Abstract: Purpose Given the fact that the Greek food and beverage (F&B) sector, along with the tourism sector, is the basis of Greek economy, the purpose of this paper is to depict the extent to which Greek F&B enterprises have embraced quality costing, as a means toward economic development and quality assurance. Since no previous research has taken place in this area, the paper aims to analyze whether the quality costing approach has been adopted, in order to achieve quality improvement and a reduction of prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 37 publications
1
26
2
1
Order By: Relevance
“…Other data collection methods like the interview and the observation were fewer in use. This is no surprise, as the interview technique is not appropriate for conducting quality cost surveys and the observation method Themes Future research suggestions Sectors, sub-sectors and units Examining CoQ in service systems (Dror, 2010), water utility organizations (Banasik and Beruvides, 2012) and public utilities including waste water, storm water and electric utilities (Banasik and Beruvides, 2012); investigating if there is a significant difference between private and publicly owned utilities with regard to CoQ (Banasik and Beruvides, 2012); assessing the cost of Six Sigma quality beyond mass manufacturing (Rodin and Beruvides, 2012); examining quality failure costs in several industry sectors (Liapis et al, 2013); studying CoQ in service organizations (Lari and Asllani, 2013;Ozkan and Karaibrahimoglu, 2013;Chopra and Singh, 2015;Zhang et al, 2015), a specific industry branch (Lari and Asllani, 2013;Kerfai et al, 2016), and in several types of industries (Lari and Asllani, 2013;Grbac et al, 2015;Chatzipetrou and Moschidis, 2017;Farooq et al, 2017;Glogovac and Filipovic, 2018;Moschidis et al, 2018); carrying out CoQ research for complex production lines (Omar and Murgan, 2014) and process configurations (Chopra and Singh, 2015); applying the Activity Based Costing (ABC) method of CoQ in the whole organization and in selected divisions (Zhang et al, 2015); exploring whether there are differences in terms of cost of poor quality in different sectors (Chiarini, 2015); studying the implementation of a quality costing system in a hospital (Uyar and Neyis, 2015); implementing the methodology of "quality cost optimization" in large and complex industries (Chopra and Singh, 2015); evaluating CoQ in retail companies (Chatzipetrou and Moschidis, 2016), departments supporting operations and quality, such as purchasing, engineering, sales and marketing…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other data collection methods like the interview and the observation were fewer in use. This is no surprise, as the interview technique is not appropriate for conducting quality cost surveys and the observation method Themes Future research suggestions Sectors, sub-sectors and units Examining CoQ in service systems (Dror, 2010), water utility organizations (Banasik and Beruvides, 2012) and public utilities including waste water, storm water and electric utilities (Banasik and Beruvides, 2012); investigating if there is a significant difference between private and publicly owned utilities with regard to CoQ (Banasik and Beruvides, 2012); assessing the cost of Six Sigma quality beyond mass manufacturing (Rodin and Beruvides, 2012); examining quality failure costs in several industry sectors (Liapis et al, 2013); studying CoQ in service organizations (Lari and Asllani, 2013;Ozkan and Karaibrahimoglu, 2013;Chopra and Singh, 2015;Zhang et al, 2015), a specific industry branch (Lari and Asllani, 2013;Kerfai et al, 2016), and in several types of industries (Lari and Asllani, 2013;Grbac et al, 2015;Chatzipetrou and Moschidis, 2017;Farooq et al, 2017;Glogovac and Filipovic, 2018;Moschidis et al, 2018); carrying out CoQ research for complex production lines (Omar and Murgan, 2014) and process configurations (Chopra and Singh, 2015); applying the Activity Based Costing (ABC) method of CoQ in the whole organization and in selected divisions (Zhang et al, 2015); exploring whether there are differences in terms of cost of poor quality in different sectors (Chiarini, 2015); studying the implementation of a quality costing system in a hospital (Uyar and Neyis, 2015); implementing the methodology of "quality cost optimization" in large and complex industries (Chopra and Singh, 2015); evaluating CoQ in retail companies (Chatzipetrou and Moschidis, 2016), departments supporting operations and quality, such as purchasing, engineering, sales and marketing…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying failure costs (Elbireer et al, 2010); identifying hidden failure costs (Elbireer et al, 2010;Duarte et al, 2018) and the hidden components of quality costs (Cheah et al, 2011;Psomas et al, 2018); examining external failure costs or externalities (Peimbert-Garcia et al, 2016); focusing on the effectiveness of specific elements of prevention and appraisal cost (Plewa et al, 2016); examining which CoQ elements practitioners should focus on (Plewa et al, 2016) and the constituents of cost of quality (prevention, appraisal, failure costs) (Chatzipetrou and Moschidis, 2016); exploring which quality costs are monitored the most and which quality costs are constantly ignored (Chatzipetrou and Moschidis, 2017), the essence and the content of each individual quality cost (Chatzipetrou and Moschidis, 2017) and the quality cost components (Chatzipetrou and Moschidis, 2018); analyzing internal and external failure cost as a loss and not as a gain (Barouch and Bey, 2018); incorporating many CoQ elements in the analysis of CoQ (Psomas et al, 2018); determining the structure of the CoQ elements (Psomas et al, 2018); studying appraisal costs (Sawan et al, 2018)…”
Section: Coq Elementsmentioning
confidence: 99%
“…It suggests that investments in preventive and evaluation measures will reduce the cost of failure, and further investments in preventive measures will reduce the costs of assessment. It is confirmed that the costs of non-compliance (internal and external costs of failure) can only be reduced by increasing expenditure on compliance activities (Ittner, 1996;Chatzipetrou and Moschidis, 2017). Improving operations of a company in the area of quality requires measuring not only costs related to quality but also their skillful analysis.…”
Section: Quality Cost Management In Smesmentioning
confidence: 99%
“…External failure costs increase as the number of defective units delivered to customers increase (Chopra and Singh, 2015). They include complaints costs in warranty, product liability costs, and loss of sales costs (Chatzipetro and Moschidis, 2017).…”
Section: Characterizing Coqmentioning
confidence: 99%